2014
DOI: 10.5194/acp-14-3771-2014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the chemical kinetic mechanisms of ozone depletion and halogen release in the polar troposphere

Abstract: The role of halogen species (e. g., Br, Cl) in the troposphere of polar regions has been investigated since the discovery of their importance for boundary layer ozone destruction in the polar spring about 25 years ago. Halogen species take part in an auto-catalytic chemical reaction cycle, which releases Br-2 and BrCl from the sea salt aerosols, fresh sea ice or snowpack, leading to ozone depletion. In this study, three different chemical reaction schemes are investigated: a bromine-only reaction scheme, which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 93 publications
2
70
0
Order By: Relevance
“…58,133136 Bloss and co-workers 134 simulated Antarctic boundary layer observations and found good replication of mean levels and diurnal cycles of observed HO x , NO x and halogen oxides. These simulations indicated that photolysis and reaction of Br with HCHO, along with ozone photolysis followed by reaction with water were the principal sources of HO x radicals.…”
Section: Recent Advances In Tropospheric Halogen Chemistrymentioning
confidence: 81%
See 3 more Smart Citations
“…58,133136 Bloss and co-workers 134 simulated Antarctic boundary layer observations and found good replication of mean levels and diurnal cycles of observed HO x , NO x and halogen oxides. These simulations indicated that photolysis and reaction of Br with HCHO, along with ozone photolysis followed by reaction with water were the principal sources of HO x radicals.…”
Section: Recent Advances In Tropospheric Halogen Chemistrymentioning
confidence: 81%
“…In the presence of significant reactive surface area, bromine explosions were found to occur after a few days induction period and with ozone depletion time scales of 1–2 days. 136 The inclusion of chlorine in this modeling study had a minor influence in ozone depletion as compared to bromine and NO x . 136 However, no snowpack source of chlorine was included in the model, as has been indicated by the study of Liao and co-workers.…”
Section: Recent Advances In Tropospheric Halogen Chemistrymentioning
confidence: 92%
See 2 more Smart Citations
“…Additionally, the current knowledge of the physical properties of the QLL and the location of liquid-like surfaces on snow grains would seem to invalidate the aforementioned assumptions on which many of the current heterogeneous models are based (Domine et al, 2013), specifically that the chemistry occurs in a liquid-like environment on snow grains. Indeed, Cao et al (2014) adopted a simplified heterogeneous chemistry mechanism in their modeling of Arctic ozone depletion, wherein they use the mass transfer of HOBr to the surface as the rate-limiting step in Br 2 production, citing the lack of suitable reaction mechanisms with which to properly simulate condensed-phase chemistry on snow/ice. Ad- …”
Section: Model Descriptionmentioning
confidence: 99%